PERCEPTIONS ABOUT TEACHER’S PROFESSION, FAMILY ENVIRONMENT, SELF-EFFICACY, AND PEERS ON INTEREST TO BECOME TEACHER AMONG FACULTY OF ECONOMICS STUDENTS - Farah Cantika Azalia; Christian Wiradendi Wolor; Osly Usman (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2023)
The purpose of this study was to determine the direct and indirect influence between the perceptions about teacher’s profession, family environment, self-efficacy, and peers on the interest in becoming a teacher in students of the FE UNJ 2019, either partially or simultaneously. This research design is a quantitative approach to the survey method. Data collection technique with a questionnaire using a Likert scale. The data analysis technique was using multiple linear regression using SPSS 24. This study used the "proportionate stratified random sampling" with the slovin formula calculation so that a sample of 162 students was obtained. The results of multiple linear regression are Y = 12.286 + 0.085X1 + 0.153X2 + 0.175X3 + 0.071X4 + 0.806. The results of the F test are F count 21,100 > F table 2.43 and a significance value of 0.000 <0.05. Then the results of the T test on all independent variables have T count > T table 1.97519 and a significance value < 0.05. So based on these calculations, both simultaneously and partially, the variable X1, X2, X3, and X4 have a positive and significant effect on Y. Perceptions about teacher’s profession, family environment, self-efficacy, and peers can explain the bond variable of interest in being a teacher by 35% while the remaining 65% is influenced by other variables outside of this study.